NATURAL WEIGHT LOSS BY SAVING CARROTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents the origin, history, distribution, biological and useful properties of carrots. The article provides information on the influence of ripening time, storage methods and regimes, and fertilization rates on the natural weight loss of carrots during storage